Cell Adhesive Character of Phenylboronic Acid-Modified Insulin and Its Potential as Long-Acting Insulin - Yui Ohno; Momoko Kawakami; Tomohiro Seki; Ryotaro Miki; Toshinobu Seki; Yuya Egawa (MDPI AG, 2019)
Phenylboronic acid (PBA) derivatives have attracted substantial attention owing to their unique character of forming dynamic covalent bonds with polyol compounds. Recent studies have shown interactions between PBA and sugar chains on the cell surface; they have interesting applications for sensors and drug delivery systems. In this study, we prepared phenylboronic acid-modified insulin (PBA-Ins) to evaluate its glucose-lowering activity and cell adhesiveness. In the case of intravenous injection, PBA-Ins showed longer glucose-lowering activity than native insulin. We hypothesized that this prolonged effect was the result of the interaction between the PBA moiety and sugar chains on the cell surface. Red blood cells (RBCs) were used as a cell model, and we confirmed PBA-Ins’s affinity for RBCs, which induced RBC agglutination. Interestingly, using an alternative PBA-Ins administration route markedly changed its glucose-lowering activity. Unlike the intravenous injection of PBA-Ins, the subcutaneous injection showed a small effect on glucose level, which indicated that a small amount of PBA-Ins was absorbed into the bloodstream. This suggested the importance of investigating the interaction between the PBA moiety and many types of cells, such as adipocytes, in subcutaneous tissues.